KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP - Zulkifli; Yunus Yunus; La Ode Akhiri Zulzaman; Muhammad Rifa'ie (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the ability of seventh-grade students at SMP Negeri 1 Bungku Selatan in writing procedure texts. Using a quantitative descriptive method with a field research approach, this study involved 75 students as the total sample. The data were collected through a written test in which students were assigned to compose a procedure text based on the given theme. The assessment focused on four aspects: title, structural completeness, linguistic features, and writing conventions. The findings show that 60% of the students (45 learners) achieved the minimum mastery criterion of 66%, while 40% (30 learners) did not meet the standard. The classical mastery level also did not reach the expected threshold of 85%. The analysis of each aspect reveals that the title aspect achieved the highest mastery (100%), whereas the structural completeness (56%), linguistic features (72%), and writing conventions (62.67%) remain below the expected level. Overall, the results indicate that students’ ability to write procedure texts is still insufficient, particularly in applying structure, linguistic features, and proper writing mechanics. These findings suggest the need for improved instructional strategies and more intensive writing practice to enhance students’ proficiency in writing procedure texts.